Rootstock on production and quality of 'Niagara Rosada' grapevine - Angelotti-Mendonca, Jessika; Moura, Mara Fernandes; Scarpare Filho, Joao Alexio; Ferracioli Vedoato, Bruna Thais [UNESP]; Tecchio, Marco Antonio [UNESP] (Soc Brasileira Fruticultura, 2018)
In Brazil, the producers have changed used rootstocks to get more vigor to scion. Rootstocks change the distribution of bud fruitfulness over grapevine shoots and the expression of the bud fruitfulness into fruit yield. Hence, these modification could alter ideal pruning length. In this way, it was evaluated bud fruitfulness, fruit yield and quality of 'Niagara Rosada' grapevine grafted onto rootstocks: 'IAC 766', 'IAC 572', 'IAC 313', 'IAC 571-6', and 'Riparia do Traviu', which 'IAC 766' is the most used rootstock in Sao Paulo State, nowadays. The evaluations were performed over three crop seasons, in a vineyard located in Louveira, SP. Two evaluations were performed in Brazilian traditional season, and one crop pruning was performed in Brazilian summer, called off-season. In traditional seasons, the bud fruitfulness was evaluated from the first to fourth bud in 2014 and to the fifth in 2015. In the off-season, bud fruitfulness was evaluated from the fifth to eighth bud. Fruit yield and quality were also evaluated over the three production cycles. Bud fruitfulness of 'Niagara Rosada' grafted onto the evaluated rootstocks showed that this characteristic was more affected by the environmental conditions, confirmed due to alteration of bud fruitfulness through production cycles. Additionally, no effect of rootstock was observed on fruit yield, and quality of 'Niagara Rosada'. Only isolated variations were detected, and these are not enough to confirm the influence of rootstocks on scion of 'Niagara Rosada'. Although no effect of rootstocks on bud fruitfulness, fruit yield and quality has been observed in the evaluated conditions, all rootstocks are recommended to be used in combination with 'Niagara Rosada'.
Keywords: Vitis labrusca L.; grape; bud fruitfulness